Ecological observations on two species of Gastropoda (Family Hygromiidae) : Monacha cantiana and Candidula gigaxii In three central Iraq provinces - H. Abd, Eman; Almukhtar, Emaduldeen (Iraqi Journal of Science, 2023)
This study was carried out on two species of the Hygromiidae family Monachacantiana and Candidula gigaxii collected from six sites in three central Iraqprovinces (Baghdad , Babylon and Karbala) . A total of 1318 individuals of Monachacantiana and 173 of Candidula gigaxii have been examined during the study periodfrom October 2013 to July 2014.The study included estimation of species relativeabundance, population density and relationship with some physico- chemicalproperties of the soil; temperature, moisture and pH.The Monacha cantiana was present at all sites but with varying numbers, whileCandidula gigaxii was confined to only three sites: Aljadiriyah and Zafaraniya atBaghdad, and Hindiya dam at Babylon. Results showed that the highest relativeabundance of Monacha cantiana was 60.8% in April 2014 at Al-Al-Hussainia,Karbala and the lowest was 12.6% in January 2014 at Zafaraniya, Baghdad. Thehighest value of relative abundance of Candidula gigaxii was 51.9 % in January 2014at the Zafaraniya , Baghdad and the lowest value was 7.3 % in March 2014 at Hindiyadam , Babylon.Population density of Monacha cantiana showed that highest value was 12.5individual / m2 in January 2014 at Al-Al-Hussainia, Karbala and the lowest value was0.8 individual / m2 in October 2013 at Aljadiriyah , Baghdad. Highest populationdensity of Candidula gigaxii was 13.6 individual / m2 in December 2013 atZafaraniya, Baghdad, and the lowest was 0.4 individual / m2 in October 2013 inAljadiriyah, Baghdad.Soil temperature varied between 7and 30 C° in January and July 2014 at Twereje,Karbala, and Aljadiriyah at Baghdad respectively. Moisture values were between 9and 33% in July and January 2014 at Alexandria and Hindiya dam, Babylon,respectively. Values of pH varied from 7.31 to 7.96 in December 2013 and July 2014at Alexandria, Babylon and Zafaraniya, Baghdad respectively. These results showedthat ecological factors may have affected abundance and population density of thesnails at all of the study sites